2021
DOI: 10.1186/s12906-021-03271-9
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine use by pediatric oncology patients before, during, and after treatment

Abstract: Background The prevalence of complementary and alternative medicine (CAM) use and the modalities used by pediatric oncology patients vary widely across studies. In addition, the changes in the use of CAM over the course of treatment are understudied. Thus, this study aimed to explore (1) CAM use by pediatric oncology patients in relation to specific time intervals and (2) communication about CAM use between parents and oncologists. Methods This ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The same study reported a substantial concern about a negative reaction from POs, preventing some patients to discuss about CM with them. 31 In our study, POs are generally open to discuss CM with both good and poor prognosis pediatric oncology patients. Based on our data, we are not able to evaluate the effect of CM on prognosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The same study reported a substantial concern about a negative reaction from POs, preventing some patients to discuss about CM with them. 31 In our study, POs are generally open to discuss CM with both good and poor prognosis pediatric oncology patients. Based on our data, we are not able to evaluate the effect of CM on prognosis.…”
Section: Discussionmentioning
confidence: 92%
“…In Switzerland, CM is often used and considered as an important subject by POs. 15,23,[29][30][31] Our survey shows that POs in Switzerland are generally aware that many of their cancer patients use CM regularly and that they are concerned about potential harmful side effects of CM. All of them indicated that it is important to know CM therapies their patients are using.…”
Section: Discussionmentioning
confidence: 92%
“…For example, a majority stated that they were encouraged to communicate openly with patients about all treatment options as a result of the knowledge they had gained about C&IM. This is of particular importance as there is still a lack of communication between patient and physician on C&IM [ 12 , 16 ]. Physicians should inform the child and his parents about potential risks and benefits of complementary therapies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, even for POs having a rather positive attitude to CIM it might be valuable for them to reflect on communication issues. The need to increase communication about CIM in pediatric oncologists is also underlined by other authors [8]. Furthermore, a generalization of the results of the evaluation to all POs in Germany cannot be made, because only small groups of POs participated in the various evaluations of the e-learning or the workshops.…”
Section: Median T2 (Min Max)mentioning
confidence: 99%